CONTINUOUS INCLUSIVE EDUCATION AND ITS SCIENTIFIC AND THEORETICAL CONCEPTUAL ISSUES - Eshnayev N.J. (European Science Publishing, 2024)
The development of individual society as a result of the acceleration of globalization, the reforms carried out in the educational system and its effectiveness, as well as the theoretical and practical issues of the organization of inclusive education are highlighted, the importance of the state and society and the responsibility of the teacher in this, professional ethics and culture, professional the issue of competence, responsibility and duty is discussed.
Keywords: Inclusive, state, society, education, teacher, learner, socialization, isolation, alienation, talent, discrimination, ability, information.